The Effect of Occupational Feminization on the Returns to Education - Gabriel, Paul E.; Schmitz, Susanne (Journal of Applied Business and Economics, 2024)
This study explores whether workers in female-dominated occupations have lower returns to schooling than workers in integrated or male-dominated occupations. Our analysis of 2023 CPS earnings data for year-round full-time workers indicates that the earnings benefits to additional schooling decline as the female density of occupations increases. This finding is consistent with the occupational feminization literature. However, we also find that females have higher returns to schooling than males in integrated and male-dominated occupational categories. Overall, women have achieved the highest labor market success in terms of returns to schooling in male-dominant occupations.